Extensive Remedial in Factoring Polynomials on STEM Learners: An Action Research - Bernal Jr., Hernando L.; Gumaru, Renz Chester R. (RIRAI Publisher, 2024)
There is a widely belief that high school students find it difficult to factor various kind of polynomials. Different ways of factoring polynomials are also highly considered in this action research. This paper chose grade 11 Science Technology Engineering and Mathematics students as respondents of the study. The study will use Extensive Remedial as the intervention for the problem. Results and Interpretation are obtained by using various appropriate statistical formulas like t-test and standard deviation. The researchers conducted this action research to verify if an extensive remedial will have a positive impact on improving the students’ ability to factor different set of polynomials